Hakam/tahkim (arbitration) in resolving family disputes: the practice in the Syariah Courts of Malaysia and Singapore - Abdul Hak, Nora (Serials Publications, 2006)
This article focuses on the provisions and the practice of ADR in family disputes by means of hakam. Resolving disputes by hakam is recognised and encouraged in Islam as a means of dispute resolution, not only in family disputes but also in other disputes such as, commercial, construction and international disputes. Provisions for family dispute resolution have been included in the Islamic Family Law Act of Malaysia and the Administration of Muslim Law Act of Singapore. Although, the two Acts are similar in their principles, the practice in Malaysia is beset with problem, while the practice in Singapore seems much more positive. The provisions of the two Acts are discussed and compared, and suggestions and recommendations to further improve the current provisions and practice are made.